More than tempt you eaudiobook - Black, Shayla (Reed Family Reckoning, 2019)
I romanced her for revenge . . . but what if she's not the enemy after all? I'm Clint Holmes. I was an ambitious guy with a busy life and a growing business. Sure, North Dakota wasn't a tropical paradise, but I was happy enough—until tragedy struck. Now the only thing that matters is finding the person responsible and making her pay. But Bethany Banks is a Harvard-educated shark used to swallowing her enemies whole while playing dangerous corporate games. How can a blue-collar oil man like me possibly beat her? The moment I lay eyes on my beautiful nemesis, the answer is obvious. I seduce her. On Maui, where she's fled, I get to know the man-eater who caused my family so much pain . . . only to find she's not the brazen ballbuster I assumed. She's skittish, secretive, vulnerable. For some reason, my instinct is to protect her. I can't abandon my plan . . . but I can't stop wanting her. Night after night, I pry her open with my touch until I'm drowning in our passion. Soon, I'm questioning everything, especially the fine line between love and hate. But when the past comes back to wreak vengeance and the truth explodes, can I prove that I'm more than tempted to love her forever? Contains mature themes.